VIGOR KEKUATAN TUMBUH BIBIT AREN TERHADAP KEKERINGAN PADA MEDIA TUMBUH CAMPURAN TANAH DAN BAHAN ORGANIK - Fathurrahman Fathurrahman; Muhammad Salim Saleh; Bunga Elim Somba (Universitas Tadulako, 2010)
The research aimed to investigate seedling vigor of sugar palm from three different locations of mother plant grown in media of soil-organic matter (OM) mixture under drought condition in pre-nursery. The experiment was conducted at the Analytical and Seed Technology Laboratories, and the Academic Garden of Agriculture Faculty, Tadulako University from June to October 2008. A Split Split Plot Design was used with three factors: mother plant place of origin consisted of three locations, i.e Parigi, Palolo and Napu. Media composition, consisted of two levels i.e Soil : OM (1:1) and soil : OM (2:1). Water status consisted of two levels i.e optimum (100% field capacity) and sub-optimum (50% field capacity). The treatments were replicated three times, thus there were 36 experimental units. The seedlings of the hole locations have the same vigor and hypothetic vigor index when growing in mixture of soil : OM (2:1), although under sub-optimum water status (50% field capacity).